Fatal Paraquat Poisoning: A Case Report (Indian Journal of Forensic Medicine & Toxicology, 2024)
Abstract: Paraquat, a widely used herbicide, is notorious for its high toxicity and limited antidotal options. This case report details the clinical presentation, management strategies, and outcomes of a patient with paraquat poisoning. A 32-year-old male presented to the emergency department with a history of intentional ingestion of paraquat. The patient exhibited signs of acute toxicity, including gastrointestinal distress, respiratory distress, and multi-organ failure. Prompt recognition and initiation of treatment were crucial in navigating the complex clinical course. The treatment protocol involved aggressive decontamination, administration of activated charcoal, and utilization of specific antidotes such as cyclophosphamide and methylprednisolone. The patient received supportive care, including mechanical ventilation and hemodynamic support. Continuous monitoring of renal and hepatic functions was implemented to detect and manage complications promptly. Despite the aggressive therapeutic approach, the patient faced significant challenges, with progressive deterioration of respiratory and renal functions. The case highlights the limited efficacy of current treatment modalities in severe paraquat poisoning. The patient eventually succumbed to multi-organ failure, underscoring the need for further research to explore alternative interventions. Paraquat poisoning remains a significant clinical challenge with high mortality rates. This case report emphasizes the importance of early recognition, aggressive decontamination, and advanced supportive care in managing paraquat toxicity. Further research is imperative to explore novel treatment strategies and improve outcomes in cases of severe paraquat poisoning.
Keywords: Paraquat; , herbicide; poisoning,; toxicology,; antidote,; multi-organ failure